Comparison of the NIST and BIPM Medium-Energy X-Ray Air-Kerma Measurements - Burns, D. T. (J Res Natl Inst Stand Technol, 2003)
The air-kerma standards used for the measurement of medium-energy x rays were compared at the National Institute of Standards and Technology (NIST) and at the Bureau International des Poids et Mesures (BIPM). The comparison involved a series of measurements at the BIPM and the NIST using the air-kerma standards and two NIST reference-class transfer ionization standards. Reference beam qualities in the range from 60 kV to 300 kV were used. The results show the standards to be in agreement within the combined standard uncertainty of the comparison of 0.35 %.